Characterization of the Aluminium Matrix Composite Reinforced with Silicon Nitride (AA6061/Si3N4) Synthesized by the Stir Casting Route - B. Ashok Kumar; M. Muthu Krishnan; A. Felix Sahayaraj; Mohamad Reda A. Refaai; G. Yuvaraj; D. Madhesh; Haiter Lenin Allasi (Advances in Materials Science and Engineering, 2022)
The current work is concerned with the synthesis of aluminium (AA6061-T6) matrix composites (AMCs) reinforced with 15 and 20 weight percentages of silicon nitride (Si3N4) particulates using the indigenously fabricated electric stir casting furnace with bottom discharge arrangement. The major concern in the synthesis of AMCs of ceramic particles with the aluminium matrix is wettability in the casting route, and it was overcome by adding 2% of magnesium in the melt, proper incorporation time, and appropriate stirring speed. The microstructure and mechanical characteristics of the synthesized AMC were analyzed. Si3N4 particles in the matrix are uniformly dispersed in the optical and scanning electron micrographs (SEM). Adding reinforcement particles of Si3N4 to the AA6061 matrix increased microhardness, macrohardness, and ultimate tensile strength significantly. Microhardness and macrohardness of the AA6161/20 wt.% Si3N4 composite were 98 VHN and 91 BHN, respectively, which were 117.8% and 111.63% higher than those of the AA6061 matrix alloy, respectively. Ultimate tensile strength (UTS) of AA6061 was 159.82 MPa which was increased to 249.12 MPa in the AA6061/20 wt.% Si3N4 composite. Percent elongation of the AA6061/Si3N4 composite was reduced with the addition of Si3N4 reinforcement.